Can aerosols influence deep tropical convection? Aerosol indirect effects in the Hector island thunderstorm. (10th December 2012) - Connolly, P. J.; Vaughan, G.; May, P. T.; Chemel, C.; Allen, G.; Choularton, T. W.; Gallagher, M. W.; Bower, K. N.; Crosier, J.; Dearden, C.
Abstract This article addresses the effects of cloud condensation nuclei on the evolution of an intense tropical convective system, known as Hector, using data taken from the ACTIVE and TWP‐ICE field campaigns, which were conducted in 2005 and 2006. The Hector thunderstorms were observed in a variety of aerosol conditions so the data serve as an ideal dataset to test whether aerosols have a significant impact on the evolution of convective clouds and precipitation. We find evidence for an aerosol effect on the storm's properties, which are reproduced with a state‐of‐the‐art mesoscale cloud‐resolving model. Including the measured aerosol concentration within the model is shown to improve the fractions skill‐score metric for every case presented in the article, thus giving us confidence that the deep convection observed during the period was indeed influenced by the aerosol entering the storm's inflow. However, we do not find a general relationship for the way aerosols affect properties such as cloud‐top height, precipitation or radiative properties, as has been suggested in previous work. The reasons for this appear to be because of the nonlinearity of interactions between neighbouring cells and because of the variability in the meteorological profiles of temperature, wind and humidity.